Performance of cardiovascular risk scores in mortality prediction ten years after Acute Coronary Syndromes - Petek,Amanda Aparecida (2019)
SUMMARY BACKGROUND The objective of this study was to evaluate the performance of the Framingham risk score (FRS) and risk score by the American College of Cardiology/American Heart Association (SR ACC/AHA) in predicting mortality of patients ten years after acute coronary syndrome (ACS). METHODS This is a retrospective cohort study that included patients aged ≥ 18 years with ACS who were hospitalized at the Coronary Intensive Care Unit (ICU) of the Botucatu Medical School Hospital from January 2005 to December of 2006. RESULTS A total of 447 patients were evaluated. Of these, 118 were excluded because the mortality in 10 years was not obtained. Thus, 329 patients aged 62.9 ± 13.0 years were studied. Among them, 58.4% were men, and 44.4% died within ten years of hospitalization. The median FRS was 16 (14-18) %, and the ACC/AHA RS was 18.5 (9.1-31.6). Patients who died had higher values of both scores. However, when we classified patients at high cardiovascular risk, only the ACC/AHA RS was associated with mortality (p <0.001). In the logistic regression analysis, both scores were associated with mortality at ten years (p <0.001). CONCLUSIONS Both FRS and SR ACC/AHA were associated with mortality. However, for patients classified as high risk, only the ACC/AHA RS was associated with mortality within ten years.